Effect of confinement on the decay of vortex rings. (6th June 2019) - Sooraj, R; Sameen, A
Abstract: The instances of vortex ring evolving in confined domains is observed in biological and engineering flows. The evolution of a vortex ring inside a non-axisymmetric confinement and the effect of this confinement on the decay of the ring is investigated in this paper. A square confinement is chosen for this purpose. The effect of confinement ratio (CR), defined as the ratio of the diameter of vortex ring to the size of confinement, is studied in detail. The asymmetry caused by the confinement on the ring is noted by measuring its properties on two different planes, namely the Y-plane and the diagonal plane. The asymmetry on the vortex ring is qualitatively observed to be dependent on CR.